'It's been quite a poor show' – exploring whether practitioners working for Improving Access to Psychological Therapies (IAPT) services are culturally competent to deal with the needs of Black, Asian and Minority Ethnic (BAME) communities. (27th February 2023) - Faheem, Afsana
Abstract: Cultural competency is a core clinical skill. Yet, psychological therapists may be inadequately trained to deal with the needs of service users from Black, Asian and Minority Ethnic (BAME) backgrounds. This can lead to dissatisfaction with mental health services, disengagement from therapy, and poorer treatment outcomes when compared to the White British population. The aim of this study was to explore whether practitioners working for Improving Access to Psychological Therapies (IAPT) services are culturally competent to deal with the needs of diverse communities. Semi-structured interviews were carried out with a range of practitioners, from early career psychological wellbeing practitioners (PWPs) to senior cognitive behavioural therapists ( n =16). Reflexive thematic analysis (RTA) was used to analyse the data, guided by a six-phase process to produce a robust pattern-based analysis. Overall, three themes were generated: (1) encountering cultural dissonance within therapy; (2) challenges in making cultural adaptations to therapy; and (3) identifying cultural competency needs. Out of sixteen participants, only nine therapists received one-day formal training throughout their therapeutic career, whilst seven reported receiving no cultural competence training at all. Overall, it appears that there is an urgent need and desire for therapists to be offered cultural competency training so that they can better serve BAME communities. Clinical implications and future recommendations are made. Key learning aims: (1) To briefly introduce cross-cultural theoretical models that may assist mental health professionals to think critically about Western notions of therapy and whether they are suited to the needs of ethnic minority communities. (2) To consider challenges IAPT practitioners encounter during therapy and identify examples of good practice. (3) To explore to what extent IAPT practitioners feel culturally competent to deal with the needs of BAME communities. (4) To encourage IAPT services and decision makers (e.g. training bodies and commissioners) to enhance cultural competence training so that practitioners can better serve ethnic minority communities.